Extensão universitária e educação básica: o caso do Programa Escola Integrada - UFMG - Natalia Fraga Carvalhais (2014)
This thesis sought to understand the relationship between the university and the basic education through the university extension. Was taken as categories of analysis two guidelines of the national policy of the Brazilian Forum Extension Pro-Chancellors of the Public Universities (FORPROEX) the inseparability between teaching, research, extension and the dialogic interaction. The locus of research was the Federal University of Minas Gerais and the Programa Escola Integrada (Integrated School Program - PEI/UFMG), which consists of an action of extension focused on promoting the relationship between the University and the policy of expanding the school day of the Municipal Department of Education of the city of Belo Horizonte (SMED) in elementary schools Programa Escola Integrada (Integrated School Program PEI/SMED). The aim of the study was to identify and analyze the policy of university extension of UFMG and the fulfillment of the above mentioned guidelines. The survey sought to further understand how the UFMG, the SMED and the schools have assessed this relationship in the development of the PEI/PBH and if this relationship has contributed to the improvement of the quality of the basic education in the city of Belo Horizonte. The research, of a qualitative nature, was developed by means of a case study of exploratory nature adopting procedures to documentary analysis and semi-structured interviews carried out with the managers the of Proex, coordination of PEI/UFMG, PEI/SMED and teachers community of three schools where the University operates. The studies highlighted the advances and setbacks of the PEI/UFMG in compliance with the inseparability between teaching, research, extension and in dialogic interaction. The results demonstrate that the inseparability depends on ensuring a stable and appropriate structure in the university and in schools, monitoring the extension actions developed with a view to the production of knowledge about the experiences and promotion of educational conditions for the college students. Regarding the dialogic interaction, the gap between the time and the distance between concepts and structural conditions of the PEI/SMED present limits to the achievement a more democratic processes affects the design, implementation and evaluation of actions by the subjects involved. Despite the fact both the UFMG as SMED and participating schools the research evaluate positively the relationship established between these instances show mutual contributions of this relationship, including improvement of the quality of basic education, referring generally to the performance and results of students in external evaluations.